SALON MANAGEMENT SYSTEM - KULUME AGNES (My University, 2024)
ABSTRACT The Unisex Salon in Mbale City, a popular destination offering a wide range of services including haircuts, styling, coloring, and spa treatments, is facing challenges in managing its daily operations due to an increasing number of clients. The current manual system for handling appointments, staff schedules, inventory, and client records is inefficient, leading to frequent errors such as missed appointments, double bookings, and inventory shortages. These issues result in reduced productivity, customer dissatisfaction, and financial losses. To address these challenges, this project proposes the development of a web-based Salon Management System specifically tailored for the salon in Mbale City. The system aims to automate and streamline various salon operations, including appointment scheduling, staff management, inventory tracking, and client record management. By replacing the manual processes with a digital platform, the system will reduce human error, improve operational efficiency, and enhance the overall customer experience. The proposed system will allow customers to book appointments online, reducing wait times and ensuring that their preferred stylists are available at the desired time. It will also provide the salon staff with an easy-to-use interface to manage their schedules, track inventory levels, and access client information quickly and accurately. Moreover, the system will generate detailed reports to help the salon management make informed decisions and optimize business operations. Implementing this Salon Management System will not only improve the efficiency and accuracy of the salon's daily operations but also position the salon as a modern, tech-savvy business in the competitive market of Mbale City. The project’s success will be measured by increased customer satisfaction, higher staff productivity, and enhanced revenue growth.